Ferroelasticity in palmierite-type(1 − x)Pb3(PO4)2 −xPb3(AsO4)2. (24th April 2017) - Bismayer, Ulli; Mihailova, Boriana; Angel, Ross
Abstract: Lead phosphate–arsenate Pb3 (P1− x As x O4 )2 undergoes an improper ferroelastic phase transition from a rhombohedral paraphase R 3 ¯ m to a monoclinic ferrophase C 2 / c leading to distinct twin boundary patterns. On cooling compounds with x larger than 0.8 undergo further transitions to monoclinic low-temperature phases, whereas the composition with x = 0.8 shows order-parameter coupling phenomena. The transformation R 3 ¯ m – C 2 / c was described on the basis of a three-state Potts model and the existence of precursors of monoclinic clusters in the rhombohedral paraphase. The system is one of the best studied improper ferroelastics. Due to its two-mode phonon behaviour the solid solution exhibits multistep temperature- as well as pressure-driven structural transformations with different length and time scales. Relevant investigations and findings of this palmierite-type material have been made by Prof E K H Salje. Some of the most prominent results from x-ray diffraction, optical microscopy and Raman scattering are reviewed, and the potential implications for domain-wall structures and engineering are discussed.